From dormant to active: Understanding triggers and pathways of demographic faultlines on group performance. - Naeem, Ramsha; Khan, Abdul Karim; Butt, Arif Nazir; Malik, Abdur Rahman (Applied Psychology: An International Review, 2026)
This study aims to identify a trigger that activates dormant demographic faultlines into activated faultlines and the downward mechanism that links the activated faultlines to diminished group performance. We theorize that intragroup entitlement beliefs are a key trigger that transforms dormant demographic faultlines into activated faultlines and that once activated, the downstream mechanism is an intragroup power struggle that undermines group performance. The study tests hypotheses through an experiment involving 74 negotiation groups and a field study of 175 organizational work groups. The data support the hypotheses. Beyond the hypothesized relationships, post hoc analyses examine a potential positive pathway whereby activated faultlines enhance intragroup communication and, in turn, improve group performance, with intragroup justice climate acting as a boundary condition. These analyses provide conditional support for this pathway.